2019
DOI: 10.1111/cas.14095
|View full text |Cite
|
Sign up to set email alerts
|

Significant epitranscriptomes in heterogeneous cancer

Abstract: Precision medicine places significant emphasis on techniques for the identification of DNA mutations and gene expression by deep sequencing of gene panels to obtain medical data. However, other diverse information that is not easily readable using bioinformatics, including RNA modifications, has emerged as a novel diagnostic and innovative therapy owing to its multifunctional aspects. It is suggested that this breakthrough innovation might open new avenues for the elucidation of uncharacterized cancer cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…Moreover, the function of RNA modification can be exerted via "reading" enzymes, such as the protein family of heterogeneous nuclear ribonucleoproteins (hnRNP) and YT521-B homology (YTH) m6A RNA binding protein 1 (YTHDF1). Those reading enzymes recognize the methylation of RNAs and bind to different proteins, which finally affect the translation efficiency and lifetime of RNA [14].…”
Section: Epitranscriptome (Rna Methylation)mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the function of RNA modification can be exerted via "reading" enzymes, such as the protein family of heterogeneous nuclear ribonucleoproteins (hnRNP) and YT521-B homology (YTH) m6A RNA binding protein 1 (YTHDF1). Those reading enzymes recognize the methylation of RNAs and bind to different proteins, which finally affect the translation efficiency and lifetime of RNA [14].…”
Section: Epitranscriptome (Rna Methylation)mentioning
confidence: 99%
“…Recent studies revealed the function of RNA modifications through the mechanisms of control of splicing, stability of transcripts, and translation process of encoded peptides [ 14 ]. Given that m6A, i.e., N6-methyl adenosine, is a predominant modification of RNA, previous studies demonstrated that the methylation reaction occurs according to consensus sequence, typically GGACU; more precisely, RRm6ACH (R notes G or A; H includes A, C, or U), or Pu (G > A) m6AC (A/C/U) (where Pu represents purine), though there are some exceptions (reviewed in [ 14 ]). The RNA modification is regulated finely by the methylation “writing” enzymes, as a forward reaction, such as Mettl3, which contains a catalytic domain, in the protein complex with Mettl14 and Wilms’ tumor 1-associating protein (Wtap) as subunits [ 14 ].…”
Section: Epitranscriptome (Rna Methylation)mentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenetic information contained in DNA exclusively includes the methylation of cytosine at the 5′ position (5mC), which exerts the control function of the downstream gene expression in the promoter and enhancer levels [ 98 ]. Nevertheless, epigenetic information in RNA was elusive until state-of-the-art technology was developed to measure the precise position in the sequence and actual modifications [ 99 ]. The application of modified mass spectrometry analysis allowed the identification of methylation information of miRNAs, suggesting its usefulness in biomarker screening in the early phases of pancreatic cancer [ 100 ].…”
Section: Exosomes Carry Mirnas Inside In Pancreatic Cancermentioning
confidence: 99%